Synthetic layered double hydroxide on biodegradable support: an efficient adsorbent for defluoridation of water - Mayadevi, S.; Kirandas, M. D.; Manilal, A. M.; Roshini, N.; Mandal, Sujata (Indian Journal of Chemical Technology, 2024)
Fluoride concentrations in drinking water above permissible levels and incidences of fluorosis among people have been reported from many parts of the world including India. Low-cost and biodegradable adsorbents are the preferred choice for the removal of fluoride from an aqueous medium. In the present study, zinc-aluminium layered double hydroxide (LDH) supported on sugarcane bagasse (raw and acid-treated) has been synthesized, characterized, and investigated for the defluoridation of water. The SEM micrographs of the supported adsorbents show good dispersion of the LDH particles on the support material. The defluoridation capacity of the LDH is enhanced by supporting it on bagasse. The adsorption capacity of supported adsorbents increased by 3-fold than the unsupported LDH adsorbent. The adsorption data have been well fitted to the Freundlich isotherm model indicating physical and multi-layer adsorption. The maximum fluoride adsorption capacity has been found to be 8.85 mg/g with 76.3% fluoride removal when the initial fluoride concentration is 11-12 mg/L. The pseudo-second-order kinetic model has been found suitable to explain the fluoride adsorption kinetics on the supported LDH adsorbents. The present study reveals that the bagasse-supported LDH adsorbent has a high potential for defluoridation of water.
Keywords: adsorption kinetics; Fluoride adsorption; Layered double hydroxide; Sugarcane bagasse